LoRa Network Performance Analysis on Landslide Monitor for Landslide Disaster Mitigation in the Greater Malang Area - Widodo, Kartiko Ardi; Dian Palevi, Bima Romadhon Parada (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
The Greater Malang region, consisting of Malang City, Batu City and Malang Regency, has a high potential for landslides, influenced by varying topography. This study shows the potential for landslides and mitigation efforts in this region. Data from the Central Statistics Agency (BPS) records the number of landslide incidents, and the East Java Government has formed a Regional Disaster Management Agency (BPBD) for risk management. A research team from the National Institute of Technology Malang developed Landslide Monitor (LSdM), a Wireless Sensor Network (WSN) using Long Range (LoRa) technology. The main focus is on Quality of Service (QoS) of LoRa networks. Test results demonstrate LSdM's capabilities in Line of Sight (LoS) and Non Line of Sight (NLoS) conditions, with LoRa frequency analysis highlighting differences in packet loss rates. LSdM is expected to improve landslide disaster risk management in Greater Malang.